A new interpretation of the experimental data for the OH+SO collision considering the recrossing reaction. (1st September 2020) - Garrido, Juan de Dios; Ellakkis, Samah; Ballester, Maikel Y.
ABSTRACT: Complexes formed in reactive collisions highlight the nature of intramolecular interactions. The present work reports a detailed quasi-classical trajectory study of the reaction OH ( v i ′, j i ′ = 1 ) + SO ( v i ″ = 0, j i ″ = 0 ) → HOSO → OH ( v f ′, j f ′ ) + SO ( v f ″, j f ″ ) considering the vibrational quantum numbers in the interval 0 ≤ v i ′ ≤ 5 and several initial relative translational energies in the range 0.2 ≤ E t r / kcalmo l − 1 ≤ 10.0 . In the study, a global DMBE PES for the ground electronic state of the HS O 2 system was used. Here, specific initial-state reactive cross sections and specific initial-state thermal rate coefficients for the recrossing reaction OH+SO are reported for the first time. Similar properties for the formation of the H + S O 2 products are also presented. The interaction between these allowed reaction channels is studied in detail. A comparison with the experimental data previously reported for the formation of H + S O 2 is shown and a new theoretical interpretation of these results, considering the recrossing reaction, is raised. GRAPHICAL ABSTRACT: